Optic nerve and chiasm hemangioblastomas in von Hippel-Lindau disease: report of 12 cases and review of the literature - Vergauwen, Evelynn; Klingler, Jan-Helge; Krüger, Marie T.; Steiert, Christine; Kuijpers, Robert; Rosahl, Steffen; Vanbinst, Anne-Marie; Andreescu, Corina Emilia; Gläsker, Sven (Frontiers in Oncology, 2024)
Optic nerve and chiasm hemangioblastomas are rare tumors, occurring sporadically or in the context of von Hippel-Lindau (VHL) disease. They have only been portrayed in isolated case reports and small cohorts. Their natural history and therapeutic strategies are only scarcely described. To better characterize these rare tumors, we retrospectively analyzed an optic nerve and chiasm hemangioblastoma series of 12 VHL patients. By combining our own experience to a review of all known cases in literature, we intended to create treatment recommendations for optic nerve and chiasm hemangioblastomas in VHL patients. We reviewed two electronic databases in the hospitals of our senior authors, searching for VHL patients with optic nerve or chiasm hemangioblastomas. Clinical data were summarized. Tumor size and growth rate were measured on contrast enhanced MRI. Comparable data were collected by literature review of all available cases in VHL patients (Pubmed, Trip, Google and Google Scholar). Of 269 VHL patients, 12 had optic nerve or chiasm hemangioblastomas. In 10 of 12 patients, tumors were diagnosed upon annual ophthalmoscopic/MRI screening. Of 8 patients who were asymptomatic at diagnosis, 7 showed absent or very slow annual progression, without developing significant vision impairment. One patient developed moderate vision impairment. Two symptomatic patients suffered from rapid tumor growth and progressive vision impairment. Both underwent late-stage surgery, resulting in incomplete resection and progressive vision impairment. One patient presented with acute vision field loss. A watchful-waiting approach was adopted because the hemangioblastoma was ineligible for vision-sparing surgery. One patient developed progressive vision impairment after watchful waiting. In the literature we found 45 patient cases with 48 hemangioblastomas. When optic nerve and chiasm hemangioblastomas are diagnosed, we suggest annual MRI follow-up as long as patients do not develop vision impairment. If tumors grow fast, threaten the contralateral eye, or if patients develop progressive vision deficiency; surgical resection must be considered because neurological impairment is irreversible, and resection of large tumors carries a higher risk of further visual decline.